2002
DOI: 10.1006/jcph.2002.7060
|View full text |Cite
|
Sign up to set email alerts
|

A Vortex Particle Method for Two-Dimensional Compressible Flow

Abstract: A vortex particle method is developed for simulating two-dimensional, unsteady compressible flow. The method uses the Helmholtz decomposition of the velocity field to separately treat the irrotational and solenoidal portions of the flow, and the particles are allowed to change volume to conserve mass. In addition to having vorticity and dilatation properties, the particles also carry density, enthalpy, and entropy. The resulting evolution equations contain terms that are computed with techniques used in some i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 45 publications
(79 reference statements)
0
43
0
1
Order By: Relevance
“…For computing derivatives near the edge of the computational domain, we developed one-sided integral operators which only look inward for information. Such a treatment is used for enforcing a nonreflecting boundary condition by Eldredge et al [9] and could be applied to wall-bounded flows as an alternative to the image treatment employed by Ploumhans and Winckelmans [15]. The dispersive character of PSE was explored and it was found that only high-order-accurate kernels should be used in these contexts.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…For computing derivatives near the edge of the computational domain, we developed one-sided integral operators which only look inward for information. Such a treatment is used for enforcing a nonreflecting boundary condition by Eldredge et al [9] and could be applied to wall-bounded flows as an alternative to the image treatment employed by Ploumhans and Winckelmans [15]. The dispersive character of PSE was explored and it was found that only high-order-accurate kernels should be used in these contexts.…”
Section: Discussionmentioning
confidence: 98%
“…These new kernels allow many new applications of PSE, particularly in wave propagation problems, but also in the baroclinic term in vortex particle methods for compressible flows [9] and other contexts not listed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on the radiation of vortex systems has been conducted in [3] (system of two vortex rings) and [4] (system of four cylindrical vortices). The computations were performed with the aid of a vortex particle method [5]. Analysis of perturbation energy of eddy flows in connection with the problem of stability was considered in [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%